Simulation of Intercalation Processes in Poorly Conductive Materials. (1st September 2022) - Zhigalenok, Yaroslav; Kokhmetova, Saule; Malchik, Fyodor; Starodubtseva, Alena; Galeyeva, Alina; Kurbatov, Andrey
Abstract : To determine the impact of the electrode composite parameters of metal-ion intercalation into host materials with poor conductivity, the processes were simulated with varying possible values of parameters. A physical model is proposed for the intercalation into an active material particle that has point contacts with an electronic conductor, considering the change in phase conductivity during intercalation. The basis of the model are the processes of electron migration through the phase of the poorly conductive material to its interface with the electrolyte, intercalation of cations from the electrolyte into the cathode material, formation of intercalated phase and its subsequent diffusive propagation into the material bulk. The finite element method implemented in COMSOL Multiphysics software was used for numerical simulation. The effect of electrical conductivity, kinetic parameters at the interfaces, mass transfer of intercalated atoms in the host material and the number of electronic contacts with cathode particle were simulated. The strong dependence of the kinetics of the de/intercalation process on the number of electronic contacts on the particle is discovered. It is shown that starting from certain values of the conductivity of the intercalation material, the reaction can be described by the equipotential surface approximation.